The future of phage biocontrol in integrated plant protection for sustainable crop production. (April 2021) - Holtappels, Dominique; Fortuna, Kiandro; Lavigne, Rob; Wagemans, Jeroen
Graphical abstract: Highlights: Understanding phage-bacterium-plant interactions is crucial for rational biocontrol. Phage treatments need to be customized according to individual pathosystems. Phage biocontrol can be integrated in smart farming, based on Internet of Things. Research on biosafety of phages is needed for regulation of biopesticides in Europe. Abstract : Bacterial phytopathogens significantly reduce crop yields and hence, pose a threat to the food supply of our increasing world population. In this context, bacteriophages are investigated as potential sustainable biocontrol agents. Here, recent advances in phage biocontrol are reviewed and considered within the framework of integrated plant protection strategies. This shows that understanding the pathogen's biology is crucial to develop a targeted strategy, tailored to individual pathosystems and driven by biotechnological insights. Moreover, the potential synergy of phages in contemporary farming practices based on the Internet of Things is proposed, potentially enabling a timely and cost-efficient treatment of plants at an early stage of the disease. Finally, these prospects are placed in the regulatory context of virus-oriented integrated pest control.